The experiences of isiMpondo speakers in learning standard isiXhosa through the formal education system : an exploratory study at a school in the Bizana district of the Eastern Cape - Maqam, Eslinah Zodwa (Rhodes University, Faculty of Humanities, School of Languages, 2015)
This study investigates the experiences of isiMpondo speakers in learning standard language through the formal education system. The sociolinguistic factors such as attitudes, language policies and language use in multilingual societies are taken into considerations. The children of non-standard language speakers such as those who speak dialects like isiMpondo have to use another language in their early years in the school system. It is articulated that the isiMpondo that the child brings to the school from the environment is not accommodated simply because it is a non-standard language; whereas the language that is used in the classroom situation is the isiXhosa variety which is a standard one. The research findings show that isiMpondo impacts on learner's education directly because they lose marks during the course of the year and during examination times if they use it. The study concludes with a recommendation that educators should honour the seven roles of educators by appropriate norms and standards. Some approaches to teaching have been suggested to be used by teachers with regard to inclusivity, as it recognises diversity, and values the following: the uniqueness of the individuals, the experiences, abilities, cultural and language backgrounds of each individual. All in all it seeks to meet the needs of the individual learner by creating a non-discriminatory teaching and learning environment.
Keywords: Language and teaching -- South Africa -- Eastern Cape -- Bizana; Native language and education; Language policy -- South Africa -- Eastern Cape -- Bizana